Efektifitas Media Kertas Kocok Terhadap Motivasi Belajar Numerasi - Yunita Yasmin Istiqomah; Dinie Anggraeni Dewi; Tuti Rahayu (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The research used is qualitative research using the case studies research method of 15 scientific journals as references and observations in grade 1 SDN Griya Bandung Indah in confirming the conclusions from the topic of learning motivation on numeracy learning that occurs in the field with various references from expert views, as revealed by the researcher that the case studies research method has very limited subjects studied but the variables studied are very broad, the material of addition and subtraction (Numeration) is problematic for grade 1 elementary school students at this time in the digital age. interesting learning and in accordance with the characteristics of low grade students or early childhood. Education is the main thing for all mankind, without education humans will lose direction and guidance in developing themselves, especially for the generation of the nation in the technological era, it is mandatory for schools to be as high as high, to provide opportunities to work and create. Education is getting higher but the motivation of grade 1 students in studying and going to school is getting lower. This is a problem in education that must be swiftly and quickly addressed, starting from comfort and a learning style that doesn't seem flat. Lower class is the beginning of learning in formal education which must continue to be given a portion of learning and development that is in accordance with the development of fun and fun low class activities for learning basic mathematics